Społeczny wymiar skutków prawnych zasiedzenia - Szuber-Bednarz, Ewa Tamara (Przegląd Politologiczny, 2018)
Acquisitive prescription is one of those constructions of civil law that are supposed to stabilize socio-economic turnover as well as govern legal transactions. To comprehensively define the issue of the consequences of acquisitive prescription it is necessary to refer to the institution of praescriptio, a legal construction characteristic of classic Roman law which is increasingly more often found in national laws. Legal constructions that are of significant importance for the members of state communities are characterized by their universality. Universality is about specific features that can be found in classical Roman law, civil law and, frequently surprisingly, in international law.